Retroperitoneal Leiomyosarcoma Presenting as Lower Gastrointestinal Bleeding: A Case Report and Review of the Literature - Dominic G. Ventura; Shyam J. Thakkar; Katie Farah (Case Reports in Gastrointestinal Medicine)
We report the first known case of a retroperitoneal leiomyosarcoma that presented with an endoscopically defined source of gastrointestinal bleeding in the colon. A 68-year-old male with a history of diverticulosis, hypertension, and hypercholesterolemia who complained of a 3-month history of abdominal pain, nausea, and intermittent hematochezia presented for evaluation of large volume hematochezia and lightheadedness. Colonoscopy revealed left-sided diverticulosis and rectal varices without stigmata of recent bleed. CT scan showed a 26 × 20 × 13 cm heterogeneous retroperitoneal mass and multiple hypodense hepatic lesions. Liver biopsy revealed leiomyosarcoma. In summary, although surgery is the mainstay of treatment, resectability has not improved significantly. Early recognition and aggressive surgery are keys to long-term survival.